Handbook on measurement, assessment, and evaluation in higher education - Secolsky, Charles; Denison, D. Brian (Routledge,Francis Group, 2018)
Increased demands for colleges and universities to engage in outcomes assessment for accountability purposes have accelerated the need to bridge the gap between higher education practice and advances in the fields of measurement, assessment and evaluation. This research handbook provides higher education administrators, student affairs personnel, institutional researchers and faculty with an integrated volume of theory, method and application